Determinants of sustained competitive advantage of born global small and medium sized enterprises in Malaysia - Wafa Shahid, 1980- , author; Kamariah Ismail, supervisor; Fakulti Pengurusan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2016